Características produtivas e estruturais do capim paiaguás diferido com períodos e alturas variáveis - Silva, Adriana Batista da (2023)
Deferring the use of pasture is a pasture management option that allows the accumulation of forage for its use, in the form of grazing, in the dry period of the year. Paiaguá grass has shown promise for this purpose. However, knowledge about changes in its structure due to management variations, such as heights and deferral periods are still scarce. Thus, the objective of this work was to compare the effect of seasons and heights on the productive and structural characteristics of the deferred paiaguás grass canopy. The combinations of two heights at the beginning of regrowth (15 and 30 cm) and three deferral times (July, August, September) were evaluated. The treatments were allocated to the experimental units in a split-plot scheme, with three replications, totaling 18 experimental units. Data analysis was performed by SAS, using Tukey's test, at 5% probability. The paiaguás grass deferred in July and August, with 15 or 30 cm in height, presented greater canopy height at the end of the deferral. Greater canopy heights after deferring were observed in paiaguás grass deferred with 30 cm in height compared to 15 cm. Higher extended tiller heights were recorded when deferring occurred in July and lower in September. The damping off index was higher in paiaguás grass deferred in July (1.59) compared to that deferred in August (1.33) and September (1.29). The paiaguás grass deferred in July presented a higher total forage accumulation (6.339 kg/ha of DM) in relation to that deferred in August (4.215 kg/ha of DM) and September (1.126 kg/ha of DM), however, with a high participation of stalks and dead forage. This resulted in lower blade:stem ratio values (0.45) in the deferred grass in July, intermediate values in the deferred grass in August (0.67) and lower in the deferred grass in September (0.85). In turn, the deferral in September reduced the accumulation of forage by 73% compared to August, which may make the accumulation of forage insufficient to feed the herd during the lean period. The height from the beginning of regrowth had less influence on the analyzed variables when the paiaguás grass remained deferred for longer periods. The paiaguás grass must be deferred in August with a height of 15 cm.